Cover Feature: Kinetics and Mechanisms of ZnO to ZIF‐8 Transformations in Supercritical CO2 Revealed by In Situ X‐ray Diffraction (ChemSusChem 10/2020). Issue 10 (8th May 2020) - Sinnwell, Michael A.; Miller, Quin R. S.; Liu, Lili; Tao, Jinhui; Bowden, Mark E.; Kovarik, Libor; Barpaga, Dushyant; Han, Yi; Kishan Motkuri, Radha; Sushko, Maria L.; Schaef, Herbert T.; Thallapally, Praveen K.
Abstract : The Cover Feature shows the transformation of ZnO to a prototypical porous framework, ZIF‐8, in supercritical carbon dioxide, highlighting a sustainable path forward for engineering targeted materials grounded in fundamental principles. Time‐resolved in situ XRD and molecular dynamics simulations are used to illuminate unique reaction mechanisms, quantifying how sacrificial templates, reaction time, solvent density, and temperature influence the transformation kinetics and resulting ZIF‐8 and ZIF‐8 heterostructures. More information can be found in the Full Paper by M. A. Sinnwell et al. on page 2602 in Issue 10, 2020 (DOI: 10.1002/cssc.202000434 ).